MHD Natural Convection Flow of Casson Ferrofluid over a Vertical Truncated Cone - Muhammad Khairul Anuar, Mohamed; Anuar, Ishak; Wan Muhammad Hilmi, Wan Rosli; Siti Khuzaimah, Soid; Alkasasbeh, Hamzeh Taha (Semarak Ilmu Publishing, 2023)
This study considers the mathematical model of MHD free or natural convection boundary layer flow of a Casson ferrofluid over a truncated cone. The set of non-linear partial differential equations that governed the model is first reduced to a simpler set of equations using the non-similar transformation. This set of equations then is solved numerically using the implicit finite difference method known as the Keller-box method. Blood and magnetite are taken as the based-fluid and the ferroparticles for the Casson ferrofluid, respectively. From the numerical study, it was found that the increase of ferroparticles volume fraction results in the increase in the skin friction coefficient and the Nusselt number while the magnetic parameter does the contrary. Further, both parameter shows diminishing effects, whereby if one of the parameter values is set to be increases, the friction between fluid and surface can be controlled by manipulating the other parameter values.